Characterization and qualitative evaluation of the vegetarian diet in Venezuelan adults - Ekmeiro-Salvador, Jesús E. (2021)
Introduction: vegetarianism is in a historical moment of expansion, proposing other ways of eating and a new type of gastronomy on the rise that require technical monitoring to evaluate its nutritional impact. Objective: to characterize the structure and qualitatively evaluate the quality of the vegetarian diet of Venezuelan adults. Material and methods: the consumption of 224 people (vegans n = 29, vegetarians n = 74, flexitarians n = 121) was evaluated using the combined technique of R24H and QFFC, in order to qualitatively compare their dietary pattern with the food guide official for the Venezuelan population. Results: only the group of vegetarians managed to adequately adjust to the guide in terms of the harmony and proportionality necessary to achieve a balanced diet. Conclusion: a well-oriented vegetarian diet can offer the real possibility of accessing all the food groups necessary to structure a balanced diet.